Implementasi Inovasi Dalam Upaya Keberlangsungan Usaha Yayasan Pembangunan Insan Farmasi Indonesia Banjarmasin - Hafizi, Ahmad; Ghalib, Saladin (Universitas Lambung Mangkurat, 2023)
This study aims to (1) determine the implementation of innovations carried out in two institutions of Yayasan Pembangunan Insan Farmasi Indonesia Banjarmasin, namely educational institutions, namely the ISFI Banjarmasin Vocational High School (SMK) and the ISFI Banjarmasin College of Health Sciences (STIKES). Complexity (Complexity), Formalization (Formalization) and Centralization (Centralization) of the innovations carried out in the two institutions.The results of the study capture the effect of Complexity, Formalization and Centralization on the implementation of innovations carried out by institutions. The implementation of the innovations carried out has the effect of hindering or facilitating the process of activities in an effort to achieve business sustainability of Yayasan Pembangunan Insan Farmasi Indonesia Banjarmasin, both at secondary level educational institutions, namely the ISFI Banjarmasin Vocational High School (SMK) and high level education, namely the College of Health Sciences (STIKES) ISFI Banjarmasin. Keywords: Implementation, Innovation, Business Continuity Efforts, Complexity, Formalization, Centralization